Nilai-Nilai Pendidikan Agama Islam dalam Novel “Kado Terbaik” Karya JS Khairen - Wahyudin Wahyudin; Zaenal Abidin; Isnaini Isnaini (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This study aims to analyze in depth the Islamic educational values contained in the novel “Kado Terbaik” by JS Khairen and to examine their relevance in shaping students’ character amid increasingly complex moral challenges among the younger generation. This research employs a qualitative approach with a library research design, in which the primary data source is the novel text, while secondary data are obtained from relevant scientific literature such as books and academic journals. Data collection is conducted through documentation techniques, while data analysis uses content analysis methods involving identification, classification, and interpretation of the values found in the text. The findings reveal that the novel embodies various Islamic educational values, including compassion, patience, responsibility, honesty, religiosity, and sincerity. These values are implicitly conveyed through the storyline, conflicts, and character development, thereby providing contextual, reflective, and affective learning experiences for readers. In addition, the presentation of stories that are closely related to real-life situations makes the moral messages easier to understand and internalize by students. The study highlights that literary works, particularly novels, have strong potential as alternative learning media in instilling character values in a practical manner. Therefore, integrating novels into Islamic education learning can serve as an innovative strategy to address moral degradation while strengthening students’ affective and spiritual dimensions in a sustainable way.